An Efficient Phosphotungstic Acid Catalysed Synthesis of 4, 5‐Dioxopyrrolidines and Study of the Mechanistic Effect of the Solvent on the Reaction. Issue 19 (22nd May 2019) - Basu, Soumyadip; Ghosh, Tanushree; Maity, Suvendu; Ghosh, Prasanta; Mukhopadhyay, Chhanda
Abstract: An efficient protocol for the synthesis of dioxopyrrolidine scaffolds has been established using phosphotungstic acid as an effective catalyst in a multicomponent reaction of aromatic primary amines, dialkyl acetylene dicarboxylates and formaldehyde at room temperature in alcohol as a green solvent. In this methodology, the reactant solvent has an important part and is involved in the reaction mechanism to increase the versatility of the product. This protocol involves environment friendly, cost effective methodology with a comparatively simple reaction mechanism. Abstract : Here we synthesized 4, 5‐Dioxopyrrolidines using Phosphotungstic Acid as a catalyst in an eco‐friendly methodology. In this methodology solvent take a very important part on the reaction. As the solvent molecule involved in the product, it increases the diversity of the product. Also the mechanism is very interesting and well studied. A total of 16 compounds have been synthesized using methanol and higher order alcohols as solvent with very good yield.